The impact of COVID-19 on walking practices in Korea: Policy implications for Urban health and physical activity resilience - Jeongsun Park; Changwoo Shon (PLoS ONE, 2025)
Background This study adopts a socio-ecological model to evaluate the individual- and community-level factors influencing walking practices among urban adults before (2018−2019) and after (2020−2021) the COVID-19 pandemic. Busan, South Korea, characterized by dense urban environments and structured health promotion systems, offers a relevant context to examine pandemic-related changes in physical activity behaviors. Methods The 2018–2021 Korea Community Health Survey was used, targeting adults aged 19 and older living in Busan Metropolitan City. Multilevel logistic regression models were constructed using data from 58,028 individuals (Level 1) and 16 administrative districts (Level 2). The binary dependent variable was walking. The independent variables included individual-level and community-level factors. Model fit was evaluated using the intraclass correlation coefficient, likelihood ratio, and −2 log likelihood. Results Individual-level variables such as sex, age, household income, subjective health status, and depression significantly correlated with walking before and after the COVID-19 pandemic. Females who perceived their health as poor or experienced depression were less likely to walk. However, the associations between age, household income, and walking practices were inconsistent. Before the pandemic, individuals who reported high trust in their neighbors were more likely to engage in walking practices. After the pandemic, those classified as obese were less likely to engage in walking practice, while individuals who engaged in alcohol consumption showed higher odds of walking practice. Moreover, participants who perceived access to public transportation as good had increased odds of walking. At the community level, pedestrian paths and social network difficulty were negatively associated with walking practice. In contrast, the availability of public sports facilities was positively associated with walking. Conclusion The COVID-19 pandemic significantly affected urban adults’ walking habits. Factors such as pedestrian paths, sports facilities, and reduced social relationship challenges helped maintain walking practices. These results highlight the need for multilevel interventions that target environmental, social, and individual determinants to promote and sustain walking during and after public health emergencies. In Korea and other high-density Asian cities, these findings provide policy-relevant evidence to guide walkability-oriented urban planning and health promotion strategies that strengthen physical activity resilience in future public health crises.